Diseno, preparacion y distribucion del VICAR, incluyendo la produccion de semilla - Jiménez, J. (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
The Central America Bean Yield and Adaptation Nursery (VICAR) maintains a permanent flow of improved materials, common commercial var., promising lines, and local controls through collaboration between CIAT and the national programs. Depending on grain color, trials are divided into 2 groups: (1) red-colored types, in which RAB 204, RAB 50, Centa Izalco, and DOR 364 are outstanding; (2) black-colored types, including ICTA Precoz 3, ICTA Ostua, Negro Huasteco, and ICTA CU 85-15. Information is given on participation countries and nursery characteristics (var. under study, exptl. design, data collection, and management). The exchange of materials should be done directly through national programs; the objectives and characteristics of the National Yield and Adaptation Nurseries (VINAR) are defined. (CIAT)